(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This paper proposes an accelerated algorithm for solving the Dirac equation. The advantage of this method is that, thanks to the successful organization of the iterative process, a significant part of the found approximate solution is expressed through an elementary function.